The K Extended Laguerre Polynomials Involving Aαr,n,kxFr r,r>2 - Adnan Khan; M. Haris Mateen; Ali Akgül; Md. Shajib Ali (Advances in Mathematical Physics)
In this manuscript, we present the generalized hypergeometric function of the type Fr r,r>2 and extension of the K Laguerre polynomial for the K extended Laguerre polynomials Ar,n,kαx. Additionally, we describe the K generating function, K recurrence relations, and KS Rodrigues formula.